Software Engineering Training: Multimedia For Video Profile Creation At The Srengseng Sawah Urban Village Office - Hidayat, Syamsu; Rifiyanti, Hafizah; Prasetya, Yuli; Firmansyah, Boy; Jaya, Rahmat; Subekti, Rino; Ardhianto, Erdiek (International Journal Of Community Service, 2025)
The community service program, titled “Software Engineering Training: Multimedia for Creating Digital Video Profiles for Srengseng Sawah Urban Village Office,” aimed to enhance the digital communication skills of local government officials and residents through training in multimedia software. This initiative addressed several key issues in Kelurahan Srengseng Sawah, including the lack of digital media skills, the absence of engaging video profiles, and insufficient use of technology in public service communication. The program was implemented in five steps: identifying needs, conducting workshops, producing videos, creating training materials, and providing post-training mentoring. Participants learned through a combination of theoretical knowledge and hands-on experience in digital storytelling, videography, video editing, and content publishing. They also explored AI editing tools and how to share their videos online, enabling them to create professional-looking profiles that showcase the village's identity and services. The outcomes included the production of official digital content, improved skills for participants, and the development of training materials for future use. In summary, this initiative demonstrates how hands-on training can enhance digital skills and promote transparency in community communication.